Photo-Switching of Protein Dynamical Collectivity - M. Xu; D. George; R. Jimenez; A. Markelz (Photonics, 2021)
We examine changes in the picosecond structural dynamics with irreversible photobleaching of red fluorescent proteins (RFP) mCherry, mOrange2 and TagRFP-T. Measurements of the protein dynamical transition using terahertz time-domain spectroscopy show in all cases an increase in the turn-on temperature in the bleached state. The result is surprising given that there is little change in the protein surface, and thus, the solvent dynamics held responsible for the transition should not change. A spectral analysis of the measurements guided by quasiharmonic calculations of the protein absorbance reveals that indeed the solvent dynamical turn-on temperature is independent of the thermal stability/photostate however the protein dynamical turn-on temperature shifts to higher temperatures. This is the first demonstration of switching the protein dynamical turn-on temperature with protein functional state. The observed shift in protein dynamical turn-on temperature relative to the solvent indicates an increase in the required mobile waters necessary for the protein picosecond motions, that is, these motions are more collective. Melting-point measurements reveal that the photobleached state is more thermally stable, and structural analysis of related RFP’s shows that there is an increase in internal water channels as well as a more uniform atomic root mean squared displacement. These observations are consistent with previous suggestions that water channels form with extended light excitation providing O2 access to the chromophore and subsequent fluorescence loss. We report that these same channels increase internal coupling enhancing thermal stability and collectivity of the picosecond protein motions. The terahertz spectroscopic characterization of the protein and solvent dynamical onsets can be applied generally to measure changes in collectivity of protein motions.

Photo Switching of Protein Dynamical Collectivity - Xu, M.; George, D. K.; Jimenez, R.; Markelz, A. G. (arXiv:1906.00893, 2019)

Protein and RNA dynamical fingerprinting - Niessen, Katherine A; Xu, Mengyang; George, Deepu K; Chen, Michael C; Ferré-D’Amaré, Adrian R; Snell, Edward H; Cody, Vivian; Pace, James; Schmidt, Marius; Markelz, Andrea G (Nature communications, 2019)

Investigation of the Isotope Shift in Protein Collective Vibrations - Luck, C.; Xu, M.; Markelz, A. (APS 2018, 2018)

Measuring Protein Intramolecular Dynamics with Terahertz Light: Functional Changes and Relevance to Biology - Xu, M.; Deng, Y.; Luck, C.; Sharma, A.; Markelz, A. (APS 2018, 2018)

Terahertz Light Fingerprints Biomolecular Dynamics - Deng, Yanting; Xu, Mengyang; Niessen, Katherine A; George, Deepu Koshy; Markelz, Andrea G (CLEO: Science and Innovations, 2018)

Escaping the Water Cage: Protein Intramolecular Vibrations and the Dynamical Transition - Xu, M. Y.; Niessen, K. A.; Deng, Y. T.; Michki, N. S.; Markelz, A. G. (Biophysical Journal, 2017)
ISI Document Delivery No.: EW3DR Times Cited: 0 Cited Reference Count: 0 Xu, Mengyang Niessen, Katherine A. Deng, Yanting Michki, Nigel S. Markelz, Andrea G. 58th Annual Meeting of the Biophysical-Society Feb 15-19, 2014 San Francisco, CA Biophys Soc NSFNational Science Foundation (NSF) [DBI 1556359, MCB 1616529]; DOEUnited States Department of Energy (DOE) [DE-SC0016317] This work was supported by NSF (DBI 1556359 and MCB 1616529), and DOE DE-SC0016317. 7 Cell press Cambridge 1542-0086 1
Keywords: Biophysics

Global Picosecond Structural Dynamics of Orange Carotenoid Protein in Photo/Chemical Activated Signaling States - Deng, Y.; Xu, M.; Liu, H.; Blankenship, R.; Markelz, A. (APS 2017 S4.002, 2017)

Importance of Protein Vibration Directionality on Function - Niessen, Katherine A.; Xu, Mengyang; Deng, Yanting; Snell, Edward H.; Markelz, Andrea G. (Biophysical Journal, 2017)
Snell, Edward/G-2055-2018 Snell, Edward/0000-0001-8714-3191 1 58th Annual Meeting of the Biophysical-Society Feb 15-19, 2014 San Francisco, CA Biophys Soc

Moving in the right direction: protein vibrations steering function - Niessen, Katherine A; Xu, Mengyang; Paciaroni, Alessandro; Orecchini, Andrea; Snell, Edward H; Markelz, Andrea G (Biophysical Journal, 2017)

Orange Carotenoid Protein Picosecond Dynamics Changes with Photo and Chemical Activation - Deng, Y. T.; Xu, M. Y.; Liu, H. J.; Blankenship, R. E.; Markelz, A. G. (Biophysical Journal, 2017)
ISI Document Delivery No.: EW3DS Times Cited: 0 Cited Reference Count: 3 Cited References: King JD, 2014, FEBS LETT, V588, P4561, DOI 10.1016/j.febslet.2014.10.024 Wilson A, 2006, PLANT CELL, V18, P992, DOI 10.1105/tpc.105.040121 Wilson A, 2008, P NATL ACAD SCI USA, V105, P12075, DOI 10.1073/pnas.0804636105 Deng, Yanting Xu, Mengyang Liu, Haijun Blankenship, Robert E. Markelz, Andrea G. 58th Annual Meeting of the Biophysical-Society Feb 15-19, 2014 San Francisco, CA Biophys Soc Liu, Haijun/0000-0003-0537-0302 14 Cell press Cambridge 1542-0086 1
Keywords: Biophysics

Temperature dependence of phonons in photosynthesis proteins - Xu, M.; Myles, D.; Blankenship, R.; Markelz, A. (APS 2017 S4.003, 2017)

Anisotropic Absorption Measurements Reveal Protein Dynamical Transition in Intramolecular Vibrations - Xu, M. Y.; Niessen, K.; Michki, N.; Deng, Y. T.; Snell, E.; Markelz, A. G. (2016 41st International Conference on Infrared, Millimeter, and Terahertz Waves, 2016)
Modeling has predicted that intramolecular structural vibrations enables proteins to access functionally important structural change. We show that the vibrational density of states and the isotropic absorption in the terahertz range are only weakly dependent on the protein functional state for several bench marking proteins. At the same time the direction of motions changes dramatically with functional state and with a resulting impact on the anisotropic absorption. Our anisotropic THz microscopy (ATM) measurements confirm this sensitivity. Here we apply the technique to the question of whether the protein dynamical transition (DT) is important to protein function. We find a strong anisotropic resonance at 70 cm(-1) rapidly increases in strength at temperatures above the DT. As these intramolecular vibrations enable protein structure to change conformation, the results suggest function will cease below DT for those proteins that require large scale conformational change.
ISI Document Delivery No.: BG7KC Times Cited: 0 Cited Reference Count: 4 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Niessen K., 2015, BIOPHYSICAL REV PETHIG R, 1995, PROTEIN SOLVENT INTE, P265 RUPLEY JA, 1991, ADV PROTEIN CHEM, V41, P37 Xu, Mengyang Niessen, Katherine Michki, Nigel Deng, Yanting Snell, Edward Markelz, A. G. Irmmw-thz Proceedings Paper 41st International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Sep 25-30, 2016 Copenhagen, DENMARK DTU, IEEE, QMC Instruments, Danish Ctr Laser Infrastructure, DTU Fotonik, Dept Photon Engn, ARL, Carl Sberg Fdn, AF Off Sci Res, Tech Univ Denmark, IEEE Microwave Theory & Tech Soc, Azpect Photon, Ekspla, Hubner HF Syst Engn, I2S, Laser Quantum, Menlo Syst, Neaspec, Springer, TeraView, Virginia Diodes Snell, Edward/G-2055-2018 Snell, Edward/0000-0001-8714-3191 345 e 47th st, new york, ny 10017 usa 2162-2027

Direct Measurements of the Long-Range Collective Vibrations of Photoactive Yellow Protein - Deng, Yanting; Xu, Mengyang; Niessen, Katherine A.; Schmidt, Marius; Markelz, Andrea G. (30th Anniversary Symposium of The Protein Society, 2016)
Long-range collective vibrations are thought to be crucial to protein functions. In the case of photoactive protein family, modeling suggests the intramolecular vibrations provide an efficient means of energy relaxation[1], feedback for enhancement of chromophore vibrations that promote structural transitions[2] and can assist in charge energy transfer[3]. As a paradigm of this family, photoactive yellow protein (PYP) is a cytoplasmic photocycling protein related to negative phototactic response to blue light in purple photosynthetic bacteria. PYP has a p-coumaric acid chromophore binding to the cysteine residue via a thioester bond, whose vibrations were found to overlap calculated vibrations of the protein scaffold. Using our unique technique of anisotropic terahertz microscopy(ATM)[4], we measure the intramolecular vibrations for PYP for the first time, including cycling between ground and blue shift (pB) states. Room temperature ATM measurements are performed in the dark and with continuous wave illumination at 488nm, resulting in a steady pB state with approximately 5% population conversion. In pB state, we find an overall decrease in the strength of resonant band in frequency range of 30-60 cm-1. Our calculated spectra using quasi-harmonic analysis indicate that our measurements are dominated by the protein vibrations, rather than the pCA chromophore, allowing us to characterize how the scaffold dynamics changes with functional states and mutations. 1. Levantino, M., et al. Nat Commun, 2015. 6. 2. Mataga, N., et al. Chem. Phys. Lett., 2002. 352(3-4): p. 220-225. 3. Fokas, A.S., et al. Photosynth. Res., 2014. 122

The Role of Dynamical Transition in Protein Function: Coupling of Protein Collective Vibrations and Water Dynamics - Xu, Mengyang; Niessen, Katherine; Deng, Yanting; Michki, Nigel; Snell, Edward; Markelz, Andrea (30th Anniversary Symposium of The Protein Society, 2016)
Computational simulations have revealed protein collective vibrations prompt structural rearrangements to accomplish biological function. However, the biological importance of collective vibrations has not been experimentally demonstrated. The attempts have been hampered by the inability to distinguish localized water or side-chain relaxational motions from protein long-range vibrations using conventional techniques. The dynamical transition (DT), extensively observed using X-ray, neutron scattering, NMR and terahertz techniques [1,2], describes a rapid increase in the temperature-dependent dynamics of critically hydrated proteins above ∼220 K, and has been attributed to thermally activated solvent motions. While some proteins lose function below the specific temperature, others do not. We suggest the difference arises from the nature of the required motions for function. Specifically, functional motions enabled by long-range vibrations will be vulnerable to DT, which require surrounding solvent to be sufficiently mobile. We explored the coupling of protein vibrations to solvent dynamics by applying a recently developed technique, anisotropy terahertz microscopy [3], to directly measure the collective vibrations for lysozyme and investigate the temperature dependence in 150-300 K range. We find long-range intramolecular vibrations occur at 220K and rapidly increase in strength with increasing temperature, consistent with enhanced access above the DT. The results suggest collective vibrations are slaved to DT, and those proteins with function reliant on these motions will cease function below DT. 1. Doster,W., et al. Phys.Rev.Lett., 2010.104(9):098101. 2. Niessen,K., et al. Biophys.Rev., 2015.7,201. 3. Acbas,G., et al. Nat.Commun., 2014.5,3076.

Terahertz optical measurements of correlated motions with possible allosteric function - Niessen, Katherine A.; Xu, Mengyang; Markelz, A. G. (Biophysical Reviews, 2015)
A suggested mechanism for allosteric response is the distortion of the energy landscape with agonist binding changing the protein structure's access to functional configurations. Intramolecular vibrations are indicative of the energy landscape and may have trajectories that enable functional conformational change. Here, we discuss the development of an optical method to measure the intramolecular vibrations in proteins, namely, crystal anisotropy terahertz microscopy, and the various approaches which can be used to identify the spectral data with specific structural motions.
19

Terahertz Optical Measurements of Correlated Motions with Possible Allosteric Function - Niessen, K. A.; Xu, M.; Markelz, A. G. (Biophysical Journal, 2015)

Probing the Stability of Fluorescent Proteins by Terahertz Spectroscopy - Xu, M. Y.; George, D. K.; Jimenez, R.; Markelz, A. G. (2014 39th International Conference on Infrared, Millimeter, and Terahertz Waves, 2014)
The higher transmission through tissues of long wavelength light motivates the development of fluorescent proteins with excitation shifted to the red. However red fluorescent proteins (RFPs) are more susceptible to photobleaching than their shorter wavelength counterparts. In particular RFPs are more susceptible to photobleaching [1]. A possible reason for this is a decrease in the structural stability of the beta barrel. Measurements of structural stability include atomic root mean squared displacement <x(2)> measured by the X-ray B-factor and neutron quasi elastic scattering. To date, X-ray measurements of RFP's do not indicate a structural stability change and systematic scattering studies have not been performed. Using THz dielectric response we examine if the picosecond structural flexibility decreases with increasing FP stability.
ISI Document Delivery No.: BF0IL Times Cited: 0 Cited Reference Count: 7 Cited References: Dean KM, 2011, BIOPHYS J, V101, P961, DOI 10.1016/j.bpj.2011.06.055 He YF, 2011, BIOPHYS J, V100, P1058, DOI 10.1016/j.bpj.2010.12.3731 Helms V, 2007, CHEMPHYSCHEM, V8, P23, DOI 10.1002/cphc.200600298 Leu BM, 2008, BIOPHYS J, V95, P5874, DOI 10.1529/biophysj.108.138198 Markelz AG, 2007, CHEM PHYS LETT, V442, P413, DOI 10.1016/j.cplett.2007.05.080 Nagy A, 2004, THERMOCHIM ACTA, V410, P161, DOI 10.1016/S0040-6031(03)00397-6 Zaccai G, 2000, SCIENCE, V288, P1604, DOI 10.1126/science.288.5471.1604 Xu, Mengyang George, D. K. Jimenez, R. Markelz, A. G. Irmmw-thz Proceedings Paper 39th International Conference on Infrared, Millimeter, and Terahertz waves (IRMMW-THz) Sep 14-19, 2014 Tucson, AZ THORLABS, Tydex, TOPTICA Photon, Bruker, Gentec EO, Lake Shore Cryotron, Ekspla, Zomega, TeraSense, Insight Product, Emcore, QMC Instruments, TeraView, NeaSpec, Advantest, MenloSystems, Traycer, Microtech Instruments Inc, LongWave Photon, Virginia Diodes Inc, ASU, MTT S, Journal Infrared Millimeter & Tera Hertz Waves, Tera Hertz Sci & Technol, Army Res Off George, Deepu/J-9882-2014 George, Deepu/0000-0003-0021-0705 345 e 47th st, new york, ny 10017 usa 2162-2027
Keywords: dynamics